Alcohol Detection in Consumer Products via POF Fiber Sensor and Spectroscopy Techniques - Kamil Abd-Rahman, M.; Saad, H.; ., . (International Journal of Engineering and Technology, 2018)
The presence of ethyl alcohol in food and beverages is impermissible in several countries. Therefore, the detection of these chemical substances is essential for preserving halal food industries. The measurement on the concentration of ethyl alcohol in water was conducted based on two techniques; where these are the POF sensing system and the absorption spectroscopic techniques. The detection of low concentrations of ethyl alcohol were performed using plastic optical fiber (POF) bent into U-shape and coil-shape, while absorption spectroscopy was used for the detection of ethyl alcohol at higher concentrations. Â The measurement of ethyl alcohol concentrations in water were in the range of 0.1 to 100.0 %v/v. Real-time measurements demonstrated that the POF sensor responded well to concentrations from 0.1 to 1.0 %v ethyl alcohol in water with sensitivity of 7.8 per % v/v ethanol concentration. While spectroscopic technique was used to detect higher ethyl alcohol concentrations in the range of 1.0 â€“ 100.0 %v/v. Several selected consumer products have shown to exhibit presence of alcohol in various concentrations below 50 %v/v. Some of these products do not have label on them and some have undeclared content of ethyl alcohol.Â Â